Selective Heating Through Y‐Junction Waveguide Designed by Acoustic Shape Optimization. Issue 1 (14th July 2022) - Lee, Han-Joo; Mancini, Julie A.; Joshipura, Ishan; Spadaccini, Christopher M.; Loh, Kenneth J.
Abstract : Unlike phononic crystals or systems designed by topology optimization, waveguides designed by shape optimization do not have voids or internal defects, making the fabrication process more suitable for additive manufacturing. By designing a Y‐junction waveguide through shape optimization, an ultrasonic wave can be controlled so that it propagates to a predetermined location just by adjusting its frequency. These demultiplexed ultrasonic waves can be used to transport signals or stimulate nearby materials. As an example, the ultrasonic wave is converted to heat at different locations, which can be applied to mechanisms that can take advantage of heating. First, shape optimization is performed on a cylindrical structure to selectively propagate ultrasonic waves of a particular frequency while attenuating others, which is analyzed through a finite element model. The numerical study results are compared with experimental measurements from samples fabricated through additive manufacturing methods. After verifying the concept, the Y‐junction waveguide is fabricated to demultiplex the wave and selectively heat different locations. The results show that the method of combining shape optimization with additive manufacturing is exceptionally simple and capable of demultiplexing ultrasonic waves, which can replace complex electrical components with single‐material waveguides. Abstract : Herein, it is aimed to achieve selective heating by designing a Y‐junction waveguide through shape optimization. The design is fabricated with Pewter alloy using additive manufacturing methods. Its acoustic performance is studied through finite element methods and compared with experimental measurements. The ultrasonic wave is converted to heat at the tip to demonstrate localized heating.